2019
DOI: 10.1016/j.afjem.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane, evidence-based medicine and associated factors: A cross-sectional study of the experiences and knowledge of Ethiopian specialists in training

Abstract: Introduction Evidence-based healthcare is a core competency for practicing healthcare practitioners and those in speciality training. In sub-Saharan Africa, little is known about the teaching of evidence-based medicine (EBM) in residency program. This survey evaluated the experiences and knowledge of Cochrane, EBM and associated factors among Ethiopian specialists in training. Methods A convenient sample of trainee specialists completed a pretested self-administered sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…Several factors affected EBM knowledge: internet access, EBM training, PubMed awareness, and familiarity with sensitivity. This finding was consistent with previous studies in Ethiopia, which identified lack of training as the most significant factor associated with physicians’ and nurses’ knowledge of EBM [ 30 ]. A study conducted in Saudi Arabia also found a significant increase in knowledge between academic levels, seminar attendees, and nonattendees [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several factors affected EBM knowledge: internet access, EBM training, PubMed awareness, and familiarity with sensitivity. This finding was consistent with previous studies in Ethiopia, which identified lack of training as the most significant factor associated with physicians’ and nurses’ knowledge of EBM [ 30 ]. A study conducted in Saudi Arabia also found a significant increase in knowledge between academic levels, seminar attendees, and nonattendees [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a review of barriers to EBP in low- and middle-income countries specifically, only 1 sub-Saharan African country was included, and in our review of the literature we could only find 6 previous studies on this topic conducted in Ethiopia. 19 , 35 , 36 , 37 , 38 To address this gap in the literature, this study aimed to assess the level of EBP among health care providers in a region of Ethiopia and to determine the factors associated with their use of EBP. The hope is that the study will provide useful information for increasing EBP implementation in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Though, Cochrane Library is the main source of systematic reviews and meta-analysis. However, it was least referred source of knowledge by this study participants 14 This study results propel the EBM movement towards; new more challenging terrain, whether residents will employ these new skills in taking care of patients. The major limitation in our study is the small sample size and the strength is use of a new questionnaire that has been previously formally validated, adopted from McColl.…”
Section: Resultsmentioning
confidence: 61%